2018
DOI: 10.3390/ijms19082405
|View full text |Cite
|
Sign up to set email alerts
|

Edema Induced by a Crotalus durissus terrificus Venom Serine Protease (Cdtsp 2) Involves the PAR Pathway and PKC and PLC Activation

Abstract: Snake venom serine proteases (SVSPs) represent an essential group of enzymatic toxins involved in several pathophysiological effects on blood homeostasis. Some findings suggest the involvement of this class of enzymatic toxins in inflammation. In this paper, we purified and isolated a new gyroxin isoform from the Crotalus durissus terrificus (Cdt) venom, designated as Cdtsp 2, which showed significant proinflammatory effects in a murine model. In addition, we performed several studies to elucidate the main pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 50 publications
0
22
0
3
Order By: Relevance
“…The recombinant collinein-1 was able to induce a discreet paw edema in mice 30 min after injection, leading to an increase in paw thickness of less than 15%. Some serine proteases have been previously tested for induction of paw edema in mice, such as BpirSP41 and BpirSP27 from Bothrops pirajai [55], BpSP-I from B. pauloensis [56], TLBm from B. marajoensis [57] and Cdtsp 2 from C. d. durissus [58], in which all of them induced mild to moderate edema formation. The edema induced by snake venoms depends mainly on the release of pro-inflammatory mediators, such as arachidonic acid metabolites (prostaglandins and leukotrienes), lipoxygenase products, histamines, serotonin and nitric oxide [59, 60].…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant collinein-1 was able to induce a discreet paw edema in mice 30 min after injection, leading to an increase in paw thickness of less than 15%. Some serine proteases have been previously tested for induction of paw edema in mice, such as BpirSP41 and BpirSP27 from Bothrops pirajai [55], BpSP-I from B. pauloensis [56], TLBm from B. marajoensis [57] and Cdtsp 2 from C. d. durissus [58], in which all of them induced mild to moderate edema formation. The edema induced by snake venoms depends mainly on the release of pro-inflammatory mediators, such as arachidonic acid metabolites (prostaglandins and leukotrienes), lipoxygenase products, histamines, serotonin and nitric oxide [59, 60].…”
Section: Discussionmentioning
confidence: 99%
“…SVSPs cause interference and imbalances of the hemostatic system by promoting specific proteolysis at various key points of the coagulation cascade [ 97 , 98 ]. Furthermore, SVSPs have been demonstrated to induce significant edema via the metabolism of arachidonic acid (AA), involving protease-activated receptors (PARs), protein kinase c (PKC), phospholipase C (PLC), and cyclooxygenase-2 (COX-2) receptors, and also induce a significant increase in malondialdehyde (MDA) levels [ 99 ]. Costa et al [ 99 ] demonstrated that SVSPs may be involved in the degradation of PAR1 and PAR2, which activate PLC and PKC to mobilize AA, while increasing oxidative stress.…”
Section: Neurotherapeutics and Preconditioning In Surgical Brain Injumentioning
confidence: 99%
“…Furthermore, SVSPs have been demonstrated to induce significant edema via the metabolism of arachidonic acid (AA), involving protease-activated receptors (PARs), protein kinase c (PKC), phospholipase C (PLC), and cyclooxygenase-2 (COX-2) receptors, and also induce a significant increase in malondialdehyde (MDA) levels [ 99 ]. Costa et al [ 99 ] demonstrated that SVSPs may be involved in the degradation of PAR1 and PAR2, which activate PLC and PKC to mobilize AA, while increasing oxidative stress. SVSPs trigger inflammatory cascades that have been implicated in SBI pathophysiology that SVMPs and PLA 2 might not successfully trigger.…”
Section: Neurotherapeutics and Preconditioning In Surgical Brain Injumentioning
confidence: 99%
“…As serinoproteases são sintetizadas como zimogênios e desempenham um papel importante na atividade patofisiológica induzida pela peçonha, pelo fato de estarem envolvidas em desordens hemostáticas, como ter influência na agregação plaquetária, no sistema fibrinolítico, na pressão sanguínea, além de poderem modular a angiogênese (AMORIM et al, 2018;COSTA et al, 2018). Ainda apresentam ação anticoagulante, pois podem ou realizar a degradação proteolítica de componentes do sistema hemostático, ou ativar e inibir de forma específica fatores da coagulação e fibrinólise.…”
Section: Serinoproteasesunclassified